The Effect of Position Promotion and Motivation on The Performance at Aceh Sharia Bank Employees Branch Office Beurawe Banda Aceh City - AMRI, Saiful; IKHBAR, Samsul; NURFARI (Indonesian Journal Economic Review (IJER), 2021)
This study aims to determine the effect of position promotion and motivation on employee performance at Bank Aceh Syariah at the Beurawe Sub-Branch Office, Banda Aceh City, the hypothesis states that the factors of job promotion (X1) and motivation (X2) affect employee performance at Bank Aceh Syariah KCP Beurawe Banda Aceh. The results of this study indicate that job promotion has a significant influence on employee motivation at Bank Aceh Syariah at the Beurawe Sub-Branch Office, Banda Aceh City. Based on the computer output above, the correlation coefficient in the study obtained a value of 0.922 where with this value there is a relationship between the independent variable and the dependent variable is 92.2%. This means that promotion factors (X1) and motivation (X2) have a very strong relationship to employee performance at Bank Aceh Syariah KCP Beurawe Banda Aceh.